Application Of Behavior Modification Using Flooding Techniques To Reduce Traumatic Children In PTSD - Ni Luh Putu Bagiartini; IGAA Noviekayatie (International Consortium of Education and Culture Research Studies, 2020)
PTSD (Post Trauma Stress Disorder) is a maladigmatic reaction that can be experienced by an individual after experiencing a traumatic event in his life. This will have an adverse effect if the individual cannot eliminate the trauma, so that it can disrupt his daily activities. The main symptom of PTSD is involuntary backlash of traumatic events in the form of intrusive dreams or